2010
DOI: 10.1063/1.3391668
|View full text |Cite
|
Sign up to set email alerts
|

Space-charge-limited hole current in poly(9,9-dioctylfluorene) diodes

Abstract: Characterization of the hole transport in blue-emitting polymers as poly(9,9-dioctylfluorene) (PFO) is strongly hindered by their large ionization potential of ∼6 eV. Using common anodes as poly(3,4-ethylenedioxythiophene)/poly(styrenesulphonic acid) leads to a strongly injection limited current. We demonstrate that molybdenum trioxide forms an Ohmic hole contact on PFO, enabling the observation of a space-charge-limited current(SCLC). This allows a direct determination of the hole mobility PFO of 1.3×10−9 m2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 38 publications
(34 reference statements)
6
76
1
Order By: Relevance
“…Similar values for were recently found for other polyfluorene derivatives. 19,23 The poor electron transport in many conjugated polymers as poly͑2-methoxy-5-3,7-dimethyloctyloxy-pphenylene vinylene͒ ͑OC 1 C 10 -PPV͒ has been explained by the presence of traps with an exponential distribution of trapping sites in energy. 24 The weak temperature of the traplimited electron current could be explained by incorporating the presence of a Gaussian DOS for free electrons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar values for were recently found for other polyfluorene derivatives. 19,23 The poor electron transport in many conjugated polymers as poly͑2-methoxy-5-3,7-dimethyloctyloxy-pphenylene vinylene͒ ͑OC 1 C 10 -PPV͒ has been explained by the presence of traps with an exponential distribution of trapping sites in energy. 24 The weak temperature of the traplimited electron current could be explained by incorporating the presence of a Gaussian DOS for free electrons.…”
mentioning
confidence: 99%
“…It was recently demonstrated that MoO 3 forms an Ohmic hole contact on poly͑9,9-dioctylfluorene͒, which has a similar HOMO level as F8BT. 19 The presence of an Ohmic contact leads to a space-charge-limited current ͑SCLC͒, which allows a direct determination of the hole mobility. With regard to the electron transport in poly͑2-methoxy-5-2-ethylhexyloxy-1,4-phenylenevinylene͒ ͑MEH-PPV͒ we recently demonstrated that the electron traps can be deactivated by addition of the n-type dopant decamethylcobaltocene ͑DMC͒.…”
mentioning
confidence: 99%
“…This evaporated MoO 3 /Au anode has been proven to be an Ohmic contact on polyfluorene derivatives with a very deep HOMO level (À6.0 eV below vacuum). [5] As a result also on the PF10TBT polymer studied here, with the HOMO level at À5.4 eV, we can be sure that this hole contact is ohmic, enabling to investigate the performance of the spincoated ZnO cathode. As a first step the electrical characteristics of the inverted devices with a solution processed ZnO electron injecting bottom contact and an evaporated MoO 3 /Au hole injecting top contact are compared to conventional devices with a PEDOT:PSS and Ba/ Al contact for hole and electron injection, respectively.…”
Section: Evaluation Of the Spincoated Zno Cathodementioning
confidence: 99%
“…Specifically, systems with evaporated molybdenum trioxide (MoO 3 ) as hole injecting contact and ZnO or TiO x as electron injecting contact have been studied extensively [3,4]. The enhanced hole injection properties of MoO 3 compared to poly (3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS), especially when injecting into polymers with very deep HOMO levels, has been abundantly proven in literature [5][6][7][8][9][10]. Furthermore, thermally evaporated vanadium pentoxide (V 2 O 5 ) has been shown to provide an ohmic injecting contact to luminescent polymers and polymer:fullerene solar cells as well [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…PFO is well known for its blue emission together with interesting electrical and electro-optical properties, making it suitable for polymer light emitting diode applications. 10,11 PFO also has a simple chemical structure but is rich in morphological features, depending on the processing conditions used, which can affect the device performance and the emission color. 12 It should be noted that polymer LEDs suffer from several disadvantages, including the lack of the stable n-type polymer necessary for device efficiency and long-term operational stability.…”
Section: Introductionmentioning
confidence: 99%